Synthesis and Characterization of a Novel Bentonite Composite Superabsorbent Resin Based on Starch - Dongfang Li; Jing Guo; Xinru Wang; Lingnan Pei; Wenjuan Li; Yanxia Liu; Yongchang Deng; Zhu Chen (Advances in Materials Science and Engineering)
A superabsorbent resin (SAR) is a functional polymer with a high water absorption capacity, which has been widely used in many fields. In this study, a modified aqueous solution polymerization process was adopted to synthesize a SAR. The optimum synthetical mass ratios of starch, bentonite, potassium persulfate (K2S2O8), and N,N′-methylene-bis-acrylamide to acrylic acid (AA) were 7.14%, 3.57%, 0.29%, and 0.057%, respectively, and the neutralization degree of AA was 50%. The molecular structure and the surface morphologies of the SAR were confirmed using Fourier transform infrared spectroscopy and scanning electron microscopy. The SAR had a water absorbency of 1300 mL/g in distilled water and 56 mL/g in 0.9 wt.% NaCl solution. The water absorption rate reached 72.65% of the maximum water absorption in 1 hour and swelled to equilibrium in 4 hours. The water retention rate was 45.86% after heating and evaporation at 150°C for 1 hour. The moisture absorption rate reached 28.2% after 10 days of placement. The modified technology provides a new synthetic method for production of SARs, which is characterized by a lack of nitrogen protection, the direct use of raw AA and potato starch, a simplified synthesis process, substantially improved efficiency, and lower production costs.